Increasing the Confidence of Local Brand Through Package Design and Information Label - Priyanto, Anif; Yeh, Hsiao-Ping (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Packaging design issues are rapidly gaining the attention of researchers as evidence indicates that most consumers are making choice decisions based on product package design. Furthermore, product information on packaging, such as ingredients and nutrition information, also increases consumers’ attention since consumers are concerned about healthy products. This study seeks to develop a theoretical model to show the effects of consumer attitudes toward visual food packaging and information labels on brand awareness and purchase intention. Six hundred fifty people completed a self-administered online questionnaire based on the literature. The empirical results show that attitudes toward visual packaging and information labels directly impact brand awareness and indirectly (through brand awareness) influence purchase intention. Surprisingly, the comparison between global and local brands shows no differentiation between global and local brands. It means the local brands can compete with the global brands. Additionally, this research indicated no differentiation between high and low business reputations. It implies that consumers in Indonesia have positive perceptions and the same favorability for any brand. This study provides managers with insights emphasizing the visual packaging design factors and informative labels to form consumers’ brand awareness and influence purchase intention.